Doing It All For My Baby: Determinants of Multidimensional Paternal Involvement with Infants. (March 2021) - Cole, Brian P.; Singley, Daniel B.; Molloy, Sonia; Ingram, Paul; Dye, Alyssa; Isacco, Anthony
The measurement of paternal involvement as a multidimensional construct has evolved with current societal trends of fathering and corresponding advanced theories. As a result, research must keep pace by continuing to examine predictors of the dynamic ways that fathers are involved with their children, particularly with infants. The current study built upon Belsky's theoretical model of determinants of parenting to posit that paternal involvement with their infants (dependent variable) will be influenced by a combination of father, child, and contextual factors (independent variables). A total of 456 participants were recruited within the United States. Paternal involvement was categorized into five subfactors from the Paternal Involvement with their Infants Scale (PIWIS). Five separate linear regressions were conducted using each of the PIWIS subscale domains as the dependent variable. Results provide support for examining paternal involvement with a multidimensional approach. Characteristics of the child, and psychosocial and relational and contextual variables of the father were uniquely related to the five domains of involvement measured by the PIWIS. Clinical and programmatic implications as well as future directions for research are discussed.